Obtaining the ultradisperse material of the Al-Mg-O system by plasma dynamic method; Gas Discharge Plasmas and Their Applications (GDP 2019) - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Rakhmatullin I. A. Ilyas Aminovich; Shanenkova Yu. L. Yuliya Leonidovna; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich (2019, 2019)
Заглавие с титульного экрана